The Realization of Commissive Speech Acts in the First Debate of South Carolina Governor Election 2018 - Dashela, Tarina; Mujiyanto, Januarius; Warsono, Warsono (Universitas Negeri Semarang, 2019)
In communication, commissive is a kind of speech acts that commit a speaker to do some future action. People should have the ability to produce and understand sentences which are appropriate in order to communicate effectively. The aims of this study are to analyze the candidates’ utterance and the candidates’ visual expression, and also to explain the roles of power and social distance in the debate. Qualitative method is applied in this study. There are five instruments which are used in this study, such as observation, recording technique, Searle and Vanderveken’s (1985) theory, Navarro and Karlin’s (2008) theory, and Trosborg’s (1994) theory. The collected data are especially in form of words, sentences, or pictures. The findings showed that there are six types of commissive speech acts used by two candidates, namely promise, assure, threaten, guarantee, offer, and refuse. It indicated that the most common commissive speech acts found is a promise. In addition, the second findings presented that there are seven types of visual expressions by two candidates, such as putting the hand in the pocket, tongue-jutting behavior, furrowed forehead, arm-distancing, palms-up, interlaced fingers, and hand-steepling. The most dominant visual expression by two candidates is palms-up. It meant that the candidates wanted to be believed or wanted to be accepted. The last findings explained that power (status) and social distance. They had equal status in power, had different perception, and had a space line in the debate. Hence, this study can be used in pragmatics class for language learners, especially they will apply appropriately commissive speech acts for the purpose of persuading voters or audiences in communication.